PENGARUH LIKUIDITAS, PROFITABILITAS, UKURAN PERUSAHAAN, RISIKO BISNIS, DAN STRUKTUR ASET TERHADAP STRUKTUR MODAL (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar Di Bursa Efek Indonesia Tahun 2016-2020 - Rukimah Ruldianah; Eny Kusumawati (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
Capital structure is one of the important topics in financial management such as creditors, shareholders, and management. Optimal capital structure is needed to ensure the survival of the company. Because the capital structure has an impact on the company's financial position which in turn will affect the value of the company. The purpose of determining the capital structure is to ensure the most optimal cost of capital and maximize shareholder welfare.This research uses quantitative research. The data used in this research is secondary data. The population of this research is a manufacturing company, totaling 192 companies. The sampling technique used the purposive sampling method, the sample was obtained from 2016 to 2020, so that the unit of analysis was obtained as many as 270 companies.This study provides empirical evidence that liquidity has an effect on capital structure, while profitability, firm size, business risk, and asset structure have no effect on capital structure.